Why not activated? The temporary protection directive and the mystery of temporary protection in the European Union - Genç, Hatice Deniz; Şirin Öner, N. Aslı (Marmara University, 2019)
Following the conflicts in former Yugoslavia, temporary protection was introduced as a crucial element of the European Union’s (EU) response to refugee crises. The EU even adopted a directive, the Temporary Protection Directive, regarding its implementation. However, despite several refugee crises, it was not activated. Building on a comprehensive analysis of official documents of European institutions and the available secondary literature, this article investigates the main reasons behind its inactivation. It reveals that the real concerns of EU Member States lay in the measures promoting a balance of efforts to provide temporary protection. In other words, Member States’ concerns over responsibility and burden sharing cast a shadow over temporary protection in the EU. The article concludes that the Directive’s inactivation indicates a crisis of fundamental principles in European integration.

Geçici koruma, Yugoslavya’daki çatışmaların ardından Avrupa Birliği’nin (AB) mu?lteci krizleri karşısında yu?ru?rlu?ğe koyacağı uygulamaların en önemli unsuru olarak ilan edildi. AB, uygulanmasına ilişkin bir ‘Geçici Koruma Yönergesi’ bile kabul etti. Ancak, bu zamana kadar yaşanan birkaç mu?lteci krizine rağmen, bu yönerge yu?ru?rlu?ğe konmadı. Avrupa kurumlarının resmi belgelerinin ve mevcut ikincil literatu?ru?n kapsamlı bir analizini temel alan bu makale, bu yönergenin yu?ru?rlu?ğe konmamasının ardındaki temel nedenleri araştırmaktadır. Makaleye göre, AB u?ye devletlerinin gerçek kaygıları, geçici koruma sağlama çabalarının dengesini destekleyen tedbirler konusunda yoğunlaşmaktadır. Başka bir deyişle, AB’de geçici koruma, u?ye devletlerin sorumluluk ve bu?tçe paylaşımı konusundaki endişelerinin gölgesi altında kalmaktadır. Makale, yönergenin yu?ru?rlu?ğe konmamasının Avrupa bu?tu?nleşmesinde bir temel ilkeler krizini gösterdiğini belirterek son bulmaktadır.
Neden yu?ru?rlu?ğe konmadı? Geçici koruma yönetmeliği ve Avrupa Birliği’nde geçici korumanın gizemi
Keywords: Asylum; European Union; Refugee Crisis; Temporary Protection; Solidarity; İltica; Avrupa Birliği; Mülteci Krizi; Geçici Koruma; Dayanışma